COVID-19 vaccination coverage and its cognitive determinants among older adults in Shanghai, China, during the COVID-19 epidemic - Wei, Lu; Zeng, Wu; Huang, Yangyang; Ye, Guoxin; Chen, Ying; Yang, Ling; Cai, Yuyang (Frontiers in Public Health, 2023)
Objectives: This study aims to examine the coverage of Coronavirus disease 2019 (COVID-19) vaccination and its cognitive determinants among older adults. Methods: A cross-sectional study was conducted using a questionnaire to survey 725 Chinese older adults aged 60 and above by questionnaire in June 2022, two months after the mass COVID-19 outbreak in Shanghai, China. The questionnaire covered demographic characteristics, COVID-19 vaccination status, internal risk perception, knowledge, and attitude towards the efficacy and safety of COVID-19 vaccines. Results: The vaccination rate was 78.3% among the surveyed individuals. Self-reported reasons for unwillingness to get vaccinated (multiple selections) were "concerns about acute exacerbation of chronic diseases after vaccination (57.3%)" and "concerns regarding vaccine side effects (41.4%)". Compared to the unvaccinated group, the vaccinated group tended to have a higher score in internal risk perception (t=2.64, P< 0.05), better knowledge of COVID-19 vaccines (t=5.84, P< 0.05), and a more positive attitude towards the efficacy and safety of COVID-19 vaccines (t=7.92, P< 0.05). The path analysis showed that the cognitive effect on vaccination behavior is relatively large, followed by the internal risk perception, and then the attitude towards COVID-19 vaccines. The more knowledgeable the participants were about COVID-19 vaccines, the more likely they received COVID-19 vaccines. In the multivariate logistic regression, the increased coverage of COVID-19 vaccination was associated with reduced age (OR=0.53 95% CI 0.43-0.66, P<0.001), being a resident in other places than Shanghai (OR=0.40, 95%CI 0.17-0.92, P< 0.05), a shorter time of lockdown (OR=0.33, 95%CI 0.13-0.83, P< 0.05), a history of other vaccines (OR=2.58, 95% CI 1.45-4.60, P< 0.01), a fewer number of chronic diseases (OR=0.49, 95%CI 0.38-0.62, P<0.001), better knowledge about COVID-19 vaccines (OR=1.60, 95% CI 1.17-2.19, P< 0.01), and a positive attitude towards COVID-19 vaccines (OR=9.22, 95% CI 4.69-18.09, P<0.001). Conclusion: Acquiring accurate knowledge and developing a positive attitude towards COVID-19 vaccines are important factors associated with COVID-19 vaccination. Disseminating informed information on COVID-19 vaccines and ensuring efficacious communication regarding their efficacy and safety would enhance awareness about COVID-19 vaccination among older adults and consequently boost their vaccination coverage.